Places of Refuge for Ships in Need of Assistance. Looking for the Best Response - Belén Sánchez Ramos (Paix et Sécurité Internationales, 2017)
The oil spills, as a result of accidents involving tankers combined with the ambiguities that affect this area of international law, have shed light on the need to take steps aimed at providing places of refuge for ships in need of assistance. In response to these disasters and to the consequences of the oil spills for the marine environment, the International Maritime Organization highlighted access to places of refuge as an issue for consideration. This article analyses the IMO Guidelines and the response of the European Union and the Mediterranean States to this issue.